Enzymatic catalysis on conducting graphite particles. - Vincent, K; Li, X; Blanford, C; Belsey, N; Weiner, J; Armstrong, F (2007)
A new concept for enzyme-catalyzed redox transformations features pairs of electron donor and acceptor enzymes attached to conducting particles. Electrons furnished by oxidation at one enzyme are used at the other. Graphite microparticles modified with hydrogenase and nitrate reductase or fumarate reductase catalyze reductions of nitrate or fumarate by H2.